P.173 Evaluating instability in Degenerative Lumbar Spondylolisthesis: objective variables versus surgeon impressions. (June 2022) - MacLean, MA; Bailey, C; Fisher, C; Rampersaud, R; Greene, R; Glennie, A
Abstract : Background: The qualitative Degenerative Spondylolisthesis Instability Classification (DSIC) system defines pre-operative instability associated with degenerative lumbar spondylolisthesis (DLS) and facilitates surgical technique selection. Objectives: (1) propose a quantitative DSIC system; (2) compare objective measures to surgeon impressions of DLS-related instability. Methods: We conducted a multi-center prospective study of 408 adult patients undergoing surgery for DLS. Variables included in the quantitative classification were assigned point-values based on evidence quality. Scores were converted to DSIC Types: 0-2 points ("Stable"; Type I), 3 points ("Potentially Unstable"; Type II), 4-5 points ("Unstable"; Type III). Surgeons documented impressions of instability using the qualitative DSIC system. Results: Five variables were included in the quantitative DSIC: presence of facet effusion, preservation of disc height (<6.5mm), translation (>4mm), kyphotic or neutral disc angle in flexion, and presence of low back pain (LBP) (>5/10 intensity). Surgeons categorized higher degrees of instability than the preliminary quantitative DSIC system, in 130 patients (42%) ( P < 0.001). Compared to procedures suggested by the quantitative DSIC system, more extensive surgical procedures were performed in 150 patients (57%) ( P < 0.001). Conclusions: A quantitative DSIC system allowed DLS-related stability to be scored and categorized. Patients potentially received more extensive surgery than warranted based on quantitative assessments of stability.